Public-Private Partnerships in Supply Chain Resilience - Hajarath, Krishna; Vummadi, Jayapal (International Journal of Supply Chain Management, 2024)
Purpose: This study examines the importance of PPPs in supply chain resilience, particularly their collaboration with the example of Microsoft and the US Department of Agriculture (USDA). More notably, the study reports on the improvement of agricultural supply chain management and food safety through the use of cloud and soft computing technologies in the context of climate change and market volatility. Methodology: The study uses case study methods based on secondary data obtained from various reports and studies in the industry. In order to measure the impact of these strategies on their ability to reduce the risk of disruptions in supply chains. Data analysis shows measurable attributes to supply chain management and sustainability in agriculture against the backdrop of technology penetration. Findings: The findings highlight that their adoption has a positive effect on the operation and flexibility of the agricultural supply chain. The data, further, indicates that as part of the collaboration, there was an improvement in data integration, prediction, and resourcing for the USDA and Microsoft partnership, which enhanced food security and adaptation to climate change. Unique Contribution to Theory, Practice and Policy: The report suggests extending the usage of such public-private collaborations for enhancement of resilient supply chains to other areas. For present and future disruptions there is need for better partnership among the government, private technology companies and adoption of sustainable practices in supply chain management.